A Virgin River Christmas - Carr, Robyn (Carr, Robyn. Virgin River series, 2021)
"Last Christmas Marcie Sullivan said a final goodbye to her husband, Bobby. This Christmas she wants to find the man who saved his life and gave her three more years to love him. Fellow marine Ian Buchanan dragged Bobby's shattered body onto a medical transport four years ago, then disappeared once their unit arrived stateside. Since then, Marcie's letters to Ian have gone unanswered. Marcie tracks Ian to the tiny mountain town of Virgin River and finds a man as wounded emotionally as Bobby was physically. As Marcie pushes her way into his reclusive life, she discovers a sweet soul beneath a rough exterior. Ian doesn't know what to make of the determined young widow who forces him to look into his painful past and the uncertain future. But it is a season of miracles, and maybe, just maybe, it's time to banish the ghosts and open his heart."--Publisher description.